2022
DOI: 10.1186/s12951-022-01507-5
|View full text |Cite
|
Sign up to set email alerts
|

Fabrication of methylene blue-loaded ovalbumin/polypyrrole nanoparticles for enhanced phototherapy-triggered antitumour immune activation

Abstract: Background Phototherapy-triggered immunogenic cell death (ICD) rarely elicits a robust antitumour immune response, partially due to low antigen exposure and inefficient antigen presentation. To address these issues, we developed novel methylene blue-loaded ovalbumin/polypyrrole nanoparticles (MB@OVA/PPY NPs) via oxidative polymerization and π–π stacking interactions. Results The as-prepared MB@OVA/PPY NPs with outstanding photothermal conversion ef… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 36 publications
0
13
0
Order By: Relevance
“…The photothermal conversion efficiency (η) of PpIX-IR-820@Lipo NPs (IR-820 concentration: 250 μg/mL) was measured as follows: PpIX-IR-820@Lipo NPs were dispersed in DIW and irradiated under a 793 nm NIR laser (250 mW/ cm 2 , 12 min). The temperature curve when the laser was on and off was recorded, and η could be calculated by the following equation: 53,54…”
Section: Experimental Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The photothermal conversion efficiency (η) of PpIX-IR-820@Lipo NPs (IR-820 concentration: 250 μg/mL) was measured as follows: PpIX-IR-820@Lipo NPs were dispersed in DIW and irradiated under a 793 nm NIR laser (250 mW/ cm 2 , 12 min). The temperature curve when the laser was on and off was recorded, and η could be calculated by the following equation: 53,54…”
Section: Experimental Methodsmentioning
confidence: 99%
“…The photothermal conversion efficiency (η) of PpIX-IR-820@Lipo NPs (IR-820 concentration: 250 μg/mL) was measured as follows: PpIX-IR-820@Lipo NPs were dispersed in DIW and irradiated under a 793 nm NIR laser (250 mW/cm 2 , 12 min). The temperature curve when the laser was on and off was recorded, and η could be calculated by the following equation: 53 , 54 where T Max and T Max,water represent the maximum equilibrium temperature for PpIX-IR-820@Lipo NPs solution and water, respectively. I is the NIR laser power density, and A 793 is the absorption of dispersion at 793 nm, measured using the time constant τ s of the system with the help of the mass ( M D ) and the heat capacity ( C D ) of DIW.…”
Section: Experimental Methodsmentioning
confidence: 99%
“…7 The introduction of immune adjuvants in cancer therapy is an effective strategy to amplify the PTTmediated antitumor immune response. 8 It demonstrated that immune adjuvants synergized with PTT could activate the APCs to trigger intense innate and adaptive immune responses. 9,10 Cytosine−phosphate−guanine oligodeoxynucleotide (CpG ODN) is a TLR9 receptor agonist located on the inner membrane of lysosome 11 and could activate DCs to induce specific cellular immunity.…”
Section: Introductionmentioning
confidence: 99%
“…These DAMPs facilitate the recruitment and activation of antigen-presenting cells (APCs) to activate T cell-mediated antitumor immune responses strongly. However, PTT-triggered ICD cannot inspire an intense immune response because of the intrinsic immunosuppressive microenvironment and poor antigen presentation . The introduction of immune adjuvants in cancer therapy is an effective strategy to amplify the PTT-mediated antitumor immune response …”
Section: Introductionmentioning
confidence: 99%
“…Compared with traditional treatments (surgery [ 5 ], chemotherapy [ 6 ], and radiation [ 7 ]), PTT had unique advantages of minimal invasion, less pain for patients, precise temporal and spatial controllability [ 4 , 8 , 9 ]. We [ 3 , 10 ] and other research groups have found that PTT was capable of inducing immunogenic cell death (ICD) of tumor cells and triggering the release of danger associated molecular patterns (DAMPs) and tumor-associated antigens (TAA), which were taken up by DC cells to activate anti-tumor immune responses [ [11] , [12] , [13] , [14] ]. Nevertheless, PPT is almost impossible to elicit robust antitumor immune response mainly due to the hypoxic tumor microenvironment as well as inefficient recognition and presentation of antigens [ 15 ].…”
Section: Introductionmentioning
confidence: 99%